The World's Oldest Temples in Göbekli Tepe and Nevali Çori, Turkey in the Light of Studies in Ontogenesis of Architecture. (2016) - Tobolczyk, Marta
Abstract: The paper is a presentation of research in Ontogenesis of Architecture i . This new field of studies within Theory of Architecture aims to formulate general rules which govern evolutionary processes in architecture. A special attention is paid to prehistoric settlements of the Near East, where during the Neolithic revolution (10 th -8 th millennium BC.) remarkable changes occurred in the art of building. Along with a man's increased ability to think in symbolic and abstractive terms various primordial forms of architecture were generated. One of the essential issues to explore is the genesis and evolution of archetypal forms of Neolithic communal/cult buildings. The purpose of the presented research is to reveal some evolutionary phenomena which determined the spatial organization of the world's oldest antecedent of a temple serving ritual and gathering purposes. This study, which is based on the comparison of structures excavated in three important prehistoric sites located near Şanliurfa in south-eastern Turkey: Göbekli Tepe (10th - 8th millennium B.C.), Nevali Çori (dated to 9th - 8th millennium B.C.) and Çayönü, can explain the origins of the oldest roofed temple. The principal result is explanation of the general rules of the Pre-Pottery Neolithic architectural order, which was used in spatial organization of the communal/cult building in the Southeastern Anatolia Region. The major conclusion is revealing the succeeding stages of evolution from ritual centres in open landscape to roofed cult buildings, which signify the transition from society of hunting-gatherers' to agriculture based community.